Antitumor effect of recombinant human interferon‐β adenovirus on esophageal squamous cell cancer in vitro. Issue 2 (3rd May 2013) - Qi, M.; Lu, D.; Li, Y.; Qin, J.; Wang, H.; Zhang, Z.; Chen, X.; Duan, F.; Ma, J.
Summary Interferon (IFN)‐β has efficient antitumor effect both in vitro and in vivo, but its clinical implication is limited by short half‐life and systemic toxicities. Gene therapy could be the choice to avoid the defects. Adenovirus vector containing human IFN‐β gene was transfected into esophageal squamous cell carcinoma KYSE150 cells. Expression of human (h)IFN‐β was detected by reverse transcription polymerase chain reaction and immunocytochemistry in KYSE150 cells. Cell growth and clonogenic assays, and flow cytometry were used to observe the antiproliferation effect and apoptosis on tumor cells, respectively. Reverse transcription polymerase chain reaction and immunocytochemistry showed obvious hIFN‐β expression in KYSE150 cells after transfection and the tumor cell proliferation was obviously inhibited through cell proliferation and clonogenic assays. Flow cytometry analysis showed 27.3% cell apoptosis in adenovirus vector containing human IFN‐β gene transfection group compared with 1.12% in empty vector control group. These findings indicate that hIFN‐β gene mediated by recombinant adenovirus may have antitumor activity against human esophageal carcinoma cell by inducing apoptosis in vitro.